Pengaruh Integritas, Kompetensi, Due Professional Care Dan Lingkungan Pengendalian Terhadap Kualitas Hasil Pemeriksaan Pada Kantor Inspektorat - Ulfa Hasanah; Endang Kartini; Agus Khazin Fauzi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This research aims to examine emotionally the influence of integrity, competence, due professional care and control environment on the quality of examination results. The data collection technique was carried out using a questionnaire. The population in this study were employees involved in inspection and audit supervision consisting of 32 Auditor positions and 18 JFP2UPD positions. After distributing the questionnaire, the samples that could be analyzed and processed were 50 samples. The analysis in this study was carried out using multiple linear regression analysis with the help of the SPSS version 21 program. The results of this study show that the integrity variable has a significant effect on the quality of examination results, competence has no significant effect on the quality of examination results, due professional care has no significant effect on the quality of examination results, the control environment has no significant effect on the quality of inspection results.